Successful bone marrow transplantation in a patient with DNA ligase IV deficiency and bone marrow failure - Bechtold Astrid; Neitzel Heidemarie; Tönnies Holger; Varon Raymonda; Zintl Felix; Seidel Joerg; Gruhn Bernd; Hoehn Holger; Schindler Detlev (Orphanet Journal of Rare Diseases, 2007)
Abstract Background DNA Ligase IV deficiency syndrome is a rare autosomal recessive disorder caused by hypomorphic mutations in the DNA ligase IV gene (LIG4). The clinical phenotype shows overlap with a number of other rare syndromes, including Seckel syndrome, Nijmegen breakage syndrome, and Fanconi anemia. Thus the clinical diagnosis is often delayed and established by exclusion. Methods We describe a patient with pre- and postnatal growth retardation and dysmorphic facial features in whom the diagnoses of Seckel-, Dubowitz-, and Nijmegen breakage syndrome were variably considered. Cellular radiosensitivity in the absence of clinical manifestations of Ataxia telangiectasia lead to the diagnosis of DNA ligase IV (LIG4) deficiency syndrome, confirmed by compound heterozygous mutations in the LIG4 gene. At age 11, after a six year history of progressive bone marrow failure and increasing transfusion dependency the patient was treated with matched sibling donor hematopoetic stem cell transplantation (HSCT) using a fludarabine-based conditioning regimen without irradiation. Results The post-transplantation course was uneventful with rapid engraftment leading to complete and stable chimerism. Now at age 16, the patient has gained weight and is in good clinical condition. Conclusion HSCT using mild conditioning without irradiation qualifies as treatment of choice in LIG4-deficient patients who have a matched sibling donor.